Long-Term Psychological Consequences of World War II Trauma Among Polish Survivors: A Mixed-Methods Study on the Role of Social Acknowledgment - Rzeszutek, Marcin; Lis-Turlejska, Maja; Krajewska, Aleksandra; Zawadzka, Amelia; Lewandowski, Michał; Szumiał, Szymon (Frontiers in Psychology, 2020)
The research on the psychological consequences of World War II (WWII) trauma has predominantly focused on concentration camp and Holocaust survivors. Only a few studies have been undertaken among civilian survivors of WWII. The purpose of this study was to examine the association between perceived social acknowledgement of WWII trauma and the level of post-traumatic stress disorder (PTSD) and depressive symptoms among Polish survivors of WWII by employing a mixed-methods design (i.e. a quantitative analysis supported by qualitative interviews). In the quantitative part, 123 participants filled out: the list of WWII-related traumatic events, the PTSD Checklist for the Diagnostic and Statistical Manual of Mental Disorders, Fifth Edition (PCL-5), the shortened version of the Geriatric Depression Scale (GDS) and the Social Acknowledgment Questionnaire (SAQ). In the qualitative part, an interpretative phenomenological analysis of participants’ reminiscences of WWII was examined. Although we observed a direct positive association between the number of WWII-related traumatic events and the intensity of PTSD and depressive symptoms, these relationships changed when we entered the social acknowledgment construct into the model. In the qualitative part, three themes relating to traumatic reminiscence emerged among the participants: parental efficacy, parental betrayal and support from the invader. The results of our study may be an adjunct to the discussion on the long-term impact of WWII trauma in Poland and the factors that hindered its social recognition. In addition, our findings are important for a better understanding of the so-called intergenerational transmission of trauma in general.